Telling the Seasons Underground: The Circadian Clock and Ambient Temperature Shape Light Exposure and Photoperiodism in a Subterranean Rodent - Flôres, Danilo E. F. L.; Jannetti, Milene G.; Improta, Giovane C.; Tachinardi, Patricia; Valentinuzzi, Veronica S.; Oda, Gisele A. (Frontiers in Physiology, 2021)
Living organisms anticipate the seasons by tracking the proportion of light and darkness hours within a day – photoperiod. The limits of photoperiod measurement can be investigated in the subterranean rodents tuco-tucos, which inhabit dark underground tunnels. Their exposure to light is sporadic and, remarkably, results from their own behavior of surface emergence. Thus, we investigated the endogenous and exogenous regulation of this behavior and its consequences to photoperiod measurement. In the field, animals carrying biologgers displayed seasonal patterns of daily surface emergence, exogenously modulated by temperature. In the laboratory, experiments with constant lighting conditions revealed the endogenous regulation of seasonal activity by the circadian clock, which has a multi-oscillatory structure. Finally, mathematical modeling corroborated that tuco-tuco’s light exposure across the seasons is sufficient for photoperiod encoding. Together, our results elucidate the interrelationship between the circadian clock and temperature in shaping seasonal light exposure patterns that convey photoperiod information in an extreme photic environment.